2017
DOI: 10.1007/s11250-017-1315-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the diversity of preferences of suburban smallholder sheep keepers for breeding rams in Ouagadougou, Burkina Faso

Abstract: Urbanisation in developing countries entails deep changes in the livestock sector and the management of animal genetic resources (AnGR). Sheep breeding around Ouagadougou (Burkina Faso) illustrates these changes and the need to coordinate genetic improvement in general and the use of crossbreeding in particular. For this, it is important to understand breeders' choices and improvement strategy, to accompany them within a national plan for AnGR management. In a context of missing market for breeding rams, a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Similarly, the lambs’ and ewe’s own body size/growth were among the most frequently stated reasons for the ranking of Mossi ewes. This suggests that these traits should be genetically improved in future breeding programs for this sheep breed, even though a study involving sheep breeders in Ouagadougou revealed that the body size had no influence on breeders’ selection decisions [45]. Genetic improvement of the body size and growth rate in the Mossi sheep while maintaining its adaptation and hardiness could reduce the threat of suburban sheep breeding around Ouagadougou through indiscriminant crossbreeding with Sahelian breed rams which are appreciated for their better growth performance, but which are less resistant to diseases [44].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the lambs’ and ewe’s own body size/growth were among the most frequently stated reasons for the ranking of Mossi ewes. This suggests that these traits should be genetically improved in future breeding programs for this sheep breed, even though a study involving sheep breeders in Ouagadougou revealed that the body size had no influence on breeders’ selection decisions [45]. Genetic improvement of the body size and growth rate in the Mossi sheep while maintaining its adaptation and hardiness could reduce the threat of suburban sheep breeding around Ouagadougou through indiscriminant crossbreeding with Sahelian breed rams which are appreciated for their better growth performance, but which are less resistant to diseases [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although libido attribute was not included in the choice experiment of the present study, it was ranked as the fifth ram selection criteria by the smallholder farmers (Table 5). Elsewhere in West Africa, Tindano et al [45] have reported a high preference for disease resistance in rams. Such preference heterogeneity for ram attributes could likely be due to differences in sheep breed, production system and sociocultural characteristics of smallholder farmers.…”
Section: Choice Preference For Sheep Traitsmentioning
confidence: 99%
“…Note, however, crossbreeding is only appropriate when animals are housed and fed appropriately so they may express their genetic potential (Zonabend et al 2017). Whereas Boer crossbreds are advantageous in body size, indigenous animals are more disease resistant as was previously reported (Tindano et al 2017). This suggests that the best larger indigenous animals, which are more adapted to the prevailing conditions, would be selected as parents of new generations.…”
Section: Descriptive Characteristics Of Herds and Animalsmentioning
confidence: 99%
“…These high market characteristics were underlined as the main drivers of a breeding programme (Gobena and Tona 2017;Tadesse et al 2015). However, animals are often left without any supervision during the day in these communal pastures, making the mating control more difficult, as underlined by Tindano et al (2017).…”
Section: Typology Of Goat Production Systemsmentioning
confidence: 99%